Administration of Lactobacillus GG to hospitalised children reduces the risk of gastrointestinal and respiratory tract infections. Issue 1 (15th December 2010) - Meadows-Oliver, Mikki
Abstract : Commentary on: Hojsak I Abdovic S Szajewska H . Lactobacillus GG in the prevention of nosocomial gastrointestinal and respiratory tract infections . Pediatrics 2010 ;125 :e1171 –7 .